Metabolic Determinants of Impaired Pulmonary Function in Patients with Newly Diagnosed Type 2 Diabetes Mellitus - Röhling, Martin; Pesta, Dominik; Markgraf, Daniel F.; Strassburger, Klaus; Knebel, Birgit; Burkart, Volker; Szendroedi, Julia; Müssig, Karsten; Roden, Michael; for the GDS study group (Experimental and Clinical Endocrinology & Diabetes, 2018)
Aims Impaired lung function associates with deterioration of glycemic control and diabetes-related oxidative stress in long-standing type 2 diabetes. We hypothesized that recent-onset type 2 diabetes patients exhibit abnormal pulmonary function when compared to glucose-tolerant controls and that the frequencies of single-nucleotide polymorphisms (SNPs), known to associate with lung dysfunction, are different between both groups.Methods Type 2 diabetes patients with a known disease duration<1 year (n=34) had similar age, sex distribution and BMI as overweight controls (n=26). Lung function was assessed by spirometry comprising predicted forced vital capacity (FVC%), predicted forced expiratory volume in one second (FEV1%) and the FEV1/FVC ratio. Multivariable linear regressions were performed to investigate group differences, which were adjusted for potential confounders such as age, sex, BMI, height and smoking status. SNP genotyping was conducted using real-time polymerase chain reaction-based allelic discrimination.Results Patients with type 2 diabetes had lower FEV1%, FEV1/FVC and VO2max (all p<0.05). Among patients with type 2 diabetes, FEV1% correlated positively with VO2max (r=0.40, p<0.05) and FEV1/FVC correlated negatively with HbA1c (r=−0.49, p<0.01). Regression analyses across the whole cohort indicated that the group differences in FEV1/FVC can be explained by the confounding effect of HbA1c. The frequencies of the SNPs rs1042713, rs1079572, rs11172113, rs12504628, rs1422795, rs1481345, rs2235910, rs2277027, rs2284746, rs4341, rs7068966, rs925284, rs993925 and rs3824658 did not differ between both groups.Conclusions Recent-onset type 2 diabetes patients exhibit reductions in features of pulmonary function, which might be at least in part resulting from glucotoxicity.
Keywords: diabetes complications; lung; single nucleotide polymorphisms; HbA1c